Ambientes de aprendizajes virtuales y su aporte en los procesos de enseñanzas-aprendizaje en estudiantes del sexto año de educación básica de la Escuela Juan E. Verdesoto, Cantón Babahoyo, Provincia de Los Ríos 2023 - Cisneros Avilés, Gloria Estefania (2023)
Virtual learning environments represent a significant transformation in contemporary education. These technology-based environments allow students to access a wide range of online educational resources and participate in interactive learning experiences. Flexibility, customization, and accessibility are key features of these environments, making them powerful tools for distance learning and online education. In addition, they promote collaboration between students and adaptation to different learning styles. However, they also pose challenges in terms of data security and privacy. Ultimately, virtual learning environments continue to evolve and play a critical role in modern education, providing innovative and accessible learning opportunities for a wide range of students. A virtual learning environment is an educational space hosted on the web, a set of computer tools that enable didactic interaction so that the student can carry out the tasks inherent to teaching such as talking, reading documents, doing exercises, formulating questions to the teacher, working as a team, etc. All this in a simulated way without any physical interaction between teachers and students. Technological dimensions, publication of materials and activities, communication or interaction between group members, collaboration to carry out group tasks. Educational dimensions, promote learning through multidirectional communication processes, it is a shared work environment for the construction of knowledge based on the active participation and cooperation of all members of the group.